IDENTIFIKASI FAKTOR RISIKO KESEHATAN LINGKUNGAN PADA PEKERJA INDUSTRI BATIK RUMAHAN DI KOTA SEMARANG - Bondhan Dwi Arum Puspo; Sulistyani Sulistyani; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Batik industry has grown a long time in Indonesia and it was one of the field of jobs for workers in cities and villages. The continued development of the batik industry in the city of Semarang, mostly uses their home  as a batik production site. Several factors that will affect the craftsman’s health problems some of which are caused by the physical environment of the house, batik production process that uses chemicals and waste that was generated. The purpose of this study was to identify the risk factors of environmental health on the workers at batik home industry in Semarang seen from batik industry conditions, the physical environment conditions, and the characteristics of workers.This study uses observational research methods with cross sectional approach. The population in this study was batik homeindustry in Semarang with a total of 38 industries then the samples are taken from the entire population. Based on the research,it was obtained that 94,1% of the industries usessynthetic dyes, 100% of the industries did not do waste treatment, 41,2% of the industries have poor ventilation, 79,4% of the industries have a bad room temperature, 64,7% of the industries have poor humidity, 70,6% of the industries have bad lighting, 100% of the industrieshave level of environmental dust exceeding the thresholdwhich was more than 0,15mg/m3, 61,8% of the workers did not use PPE, 4,0% of the workers experiencingcomplaints on their head, 6,7%of the workers experiencing complaints on their eye, 27,0% of the workers experiencingcomplaints on their skin, 2,6% of the workers experiencingcomplaints on their nose, 1,3% of the workers experiencingcomplaints on their throat, 33,7% of the workers experiencingcomplaints on their hand,8,1% of the workers experiencingcomplaints on their shoulder, 8,1% of the workers experiencingcomplaints on their waist, and 8,1% of the workers experiencingcomplaints on their leg. The conclusion of this study was all industries did not do waste treatment, the worst physical environmentconditions was the room temperature79,4% of the industries did not meet the requirements(18-30oC) andthe highest worker complaints are complaints on their hand which was 33.4% of all complaints.